PERAMALAN DAN ANALISIS PERPUTARAN PERSEDIAAN PRODUK DAPUR KERIPIK RIDA DENGAN METODE SINGLE MOVING AVERAGE - Tri Wulandari; Nuriadi Manurung; Sudarmin (LPPM Universitas Abdurrab, 2026)
Rida Chip Kitchen is a business engaged in the production and sale of various types of chips. The problem faced by Rida Chip Kitchen is the difficulty in determining the optimal inventory level for each period, resulting in excessive inventory storage that increases operational costs and inventory shortages that lead to lost sales opportunities over the past seven months. Production is carried out without clear planning, leading to an imbalance between demand and inventory, as well as the risk of excess or shortage of inventory due to the absence of accurate forecasts. The Single Moving Average (SMA) method is the simplest type of Moving Average that does not use weighting in its calculations of closing price movements. The research method used in this study is a quantitative research method. From the analysis results at Rida's Chip Kitchen, it is possible to predict product demand more accurately, improve product availability, and reduce the risk of customers switching to competitors due to stock shortages